PENERAPAN MEDIA KONKRET KUE DAN BISKUIT BERBENTUK BANGUN DATAR DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS 2 DI SDN 21 SIJUNJUNG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on the observation results, it was found that the mathematics learning outcomes of second-grade students at SDN 21 Sijunjung on the topic of plane figures were still very low. The purpose of this study was to improve students’ learning outcomes in mathematics in the second grade at SDN 21 Sijunjung.This study was a classroom action research consisting of four stages: planning, implementation, observation, and reflection. The subjects of this study were 15 second-grade students. The research instruments used were observation sheets and test sheets. The results of the study indicate that the application of concrete media in the form of cakes and biscuits shaped like plane figures was proven to improve the mathematics learning outcomes of second-grade students at SDN 21 Sijunjung in the 2025/2026 academic year. In Cycle I, learning mastery was still 33% with an average score of 62.00. However, in Cycle II there was a significant improvement, where mastery reached 87% with the average score increasing to 88.67.